2014
DOI: 10.2147/idr.s39639
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus – antimicrobial resistance and the immunocompromised child

Abstract: Children with immunocompromising conditions represent a unique group for the acquisition of antimicrobial resistant infections due to their frequent encounters with the health care system, need for empiric antimicrobials, and immune dysfunction. These infections are further complicated in that there is a relative paucity of literature on the clinical features and management of Staphylococcus aureus infections in immunocompromised children. The available literature on the clinical features, antimicrobial suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 112 publications
0
11
0
Order By: Relevance
“…Among children with malignancy, congenital heart disease or liver transplant recipients, S . aureus accounts for up for 9–13%, 13% and 20% of blood stream infections, respectively [ 4 , 6 8 ]. The effective prevention is greatly impeded, as S .…”
Section: Introductionmentioning
confidence: 99%
“…Among children with malignancy, congenital heart disease or liver transplant recipients, S . aureus accounts for up for 9–13%, 13% and 20% of blood stream infections, respectively [ 4 , 6 8 ]. The effective prevention is greatly impeded, as S .…”
Section: Introductionmentioning
confidence: 99%
“…Children with immunocompromising conditions are a unique population in their acquisition of antimicrobial-resistant infections because of their exposure to empirical antimicrobials, frequent encounters with health-care settings, and overall immune dysfunction. 63 , 64 , 65 , 66 …”
Section: Discussionmentioning
confidence: 99%
“…Essentially, S. aureus is an important cause of community-acquired (CA) and hospital-acquired (HA) human infections, and a potential strategy for controlling these infections is by eliminating or minimizing nasal carriage, such as those with intermittent and persistent carriage of the same or different S. aureus strains [ 5 ]. A more worrisome dimension is the isolation of nasal S. aureus in vulnerable groups such as the immunocompromised and immunosuppressed [ 6 ]. For instance, a study by Leshem et al [ 7 ] reported identical S. aureus strains in 80% of infants and their mothers.…”
Section: Introductionmentioning
confidence: 99%